Wrapping VRXQuery with self-adaptive fuzzy capabilities - Lo, Anthony; Kianmehr, Keivan; Kaya, Mehmet; Oezyer, Tansel; Alhajj, Reda (Ieee Computer Soc, 2007)
This paper addresses the development of a plug and run wrapper to incorporate fuzziness into VRXQuery, the querying facility of VIREX which is a user-friendly system for transforming and querying relational data as XML. Our basic argument is not to force the underlying XML data to incorporate fuzziness. Rather, fuzziness is smoothly supported in a novel plug and run manner via a wrapper. Either the user specifies the membership functions for the elements/attributes to be queried as fuzzy, or multi-objective genetic algorithm is used to automatically decide on and optimize the membership functions. The interface of VIREX has been expanded to allow specifying queries with fuzziness. Then, queries expressed in VRXQuery empowered with fuzziness am translated into corresponding XQuery code, which is ran on the underlying XML and the returned result is translated into a fuzzy representation; translation into SQL is also possible. The user is given the choice to display the result either as colored-text or in graphical format.
IEEE/WIC/ACM International Conference on Web Intelligence -- NOV 02-05, 2007 -- Silicon Valley, CA